2021
DOI: 10.1101/2021.04.30.21256370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mixed methods systematic review and metasummary about barriers and facilitators for the implementation of cotrimoxazole and isoniazid – preventive therapies for people living with HIV

Abstract: Background: Cotrimoxazole and isoniazid preventive therapy (CPT, IPT) have been shown to be efficacious therapies for the prevention of opportunistic infections and tuberculosis (TB) among people living with human immunodeficiency virus (HIV). Despite governments' efforts to translate World Health Organization recommendations into practice, implementation remains challenging. This review aimed to explore and compare CPT and IPT with respect to similarities and differences of barriers identified across high TB/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…Several other studies pooled together in a systematic review on several continents also identified age to be associated with adherence to other interventions which are also normally given to HIV patients (Müller & Velez Lapão, 2021).This study found a statistically significant relationship between age and adherence to both ART and co-trimoxazole preventive therapy (CPT) in the bivariate analysis as was revealed in other studies such as that of B. Addo et al, 2018 in Ashanti region which also found older age to be more likely associated with non-adherence to ART.…”
Section: Potential Risk Factors For Toxoplasmosis Among Art Clients A...mentioning
confidence: 97%
See 4 more Smart Citations
“…Several other studies pooled together in a systematic review on several continents also identified age to be associated with adherence to other interventions which are also normally given to HIV patients (Müller & Velez Lapão, 2021).This study found a statistically significant relationship between age and adherence to both ART and co-trimoxazole preventive therapy (CPT) in the bivariate analysis as was revealed in other studies such as that of B. Addo et al, 2018 in Ashanti region which also found older age to be more likely associated with non-adherence to ART.…”
Section: Potential Risk Factors For Toxoplasmosis Among Art Clients A...mentioning
confidence: 97%
“…However, religious beliefs may affect coping mechanisms and could in turn influence the acceptability for and adherence to any form of long term treatment. Living with family members who offer the necessary support may impact positively on adherence as compared to living alone whereby the impetus for taking medications may sometimes be lacking (Müller & Velez Lapão, 2021). In the same way, living with a stigmatizing and unsupportive family may equally impact negatively on adherence to treatment, as was shown in one study in an African country where some respondents reported that they had ever experienced instances where their family members deliberately discarded their medications (Müller & Velez Lapão, 2021).…”
Section: Potential Risk Factors For Toxoplasmosis Among Art Clients A...mentioning
confidence: 99%
See 3 more Smart Citations